Understanding COVID-19 Vaccine Hesitancy in Ethnic Minorities Groups in the UK - Naqvi, Maryam; Li, Lan; Woodrow, Michael; Yadav, Punam; Kostkova, Patty (Frontiers in Public Health, 2022)
COVID-19 vaccines have been developed and administered at record pace in order to curtail the impact of the COVID-19 pandemic. Vaccine hesitancy has impacted uptake unequally across different groups. This study explores the drivers for vaccine hesitancy in ethnic minority groups in the UK, the impact of social media on vaccine hesitancy and how vaccine hesitancy may be overcome. Twelve semi-structured interviews were conducted, coded and thematically analyzed with participants from ethnic minority groups in the UK who identified as vaccine hesitant. Social media played a significant role in vaccine hesitancy. For those who considered themselves healthy, seeing misinformation of extreme side effects relating to COVID-19 vaccinations on social media resulted in the opinion that the risk of vaccination is greater than risk from COVID-19 infection. For women, misinformation on social media regarding fertility was a reason for delaying or not getting vaccinated. Access and trust of sources of information outside of social media increased likelihood of vaccination. This study identified the broad spectrum of views on vaccine hesitancy in ethnic minority groups in the UK. Enabling factors such as a desire to travel, and positive public health messaging can increase vaccine uptake, whereas a lack of trusted sources of information may cause vaccine hesitancy. Further research is required to combat misinformation and conspiracy theories. Effective methods include actively responding and disproving the misinformation. For an inclusive vaccination programme that reduces health inequality, policy makers should build trust amongst marginalized communities and address their concerns through tailored public health messaging.